Turkey and the European Union Christian and secular images of Islam - Levin, Paul T. (Palgrave Macmillan, 2011)
This book carefully examines the historical roots of contemporary Western prejudices against both Muslims and Turks, and presents an original theory of collective identity as dramatic re-enactment as a means of understanding the remarkable persistence of medieval stereotypes